LEGAL CONSEQUENCES: DISSOLUTION OF MARRIAGE DUE TO DIVORCE SUITS FROM DIFFERENT RELIGIONS (Study Decision Number: 55/Pdt.G/2022/PN.Tjk): AKIBAT HUKUM : BUBARNYA PERKAWINAN KARENA GUGATAN PERCERAIAN YANG BERBEDA AGAMA (Putusan Pengadilan Nomor : 55/Pdt.G/2022/PN.Tjk) - Recca Ayu Hapsari; Reza Apiat (Universitas Majalengka, 2024)
Marriage is the behavior of creatures created by God Almighty so that life in the natural world can reproduce. Because humans are intelligent creatures, marriage is one of the orderly and sacred cultures that follows the development of human culture in the development of social life. Law Number 1 of 1974 concerning Marriage, namely regarding the maintenance of children, joint assets and maintenance/expenses for the wife and children. The responsibility of parents who have divorced for the support of minor children is that children who are not yet mumayyiz (12 years old) have the right to receive hadhanah from their mother, unless the mother dies, then her position is replaced by women in a straight line up from the mother. , women in a straight line upwards from the father, sister of the child in question. Implementation of the Divorce Process in the District Court Study Decision Number: 55/Pdt.G/2022/PN. Tjk is the same as the process is not much different from How to file a divorce suit by a Muslim couple. Non-Muslim couples are required to file a divorce suit at the district court, so that their divorce is valid in the eyes of the law of the nation and state. With supporting reasons for the divorce lawsuit, the divorce lawsuit will be granted by the court.